60 Years of Practice, Research, and Teaching in Family Psychology and Family Therapy. Issue 4 (7th August 2016) - L'Abate, Luciano
ABSTRACT: Recent theoretical and empirical evidence as well as experimental and practical highlights from 60 years of clinical practice, research, and teaching in family therapy are summarized. This summary contains recent highlights that remain in my memory more vividly than others. I shall start with selected models of Relational Competence Theory (RCT), including variations on the theme of the Deadly Drama Triangle and their workbook applications.